Endogenous sunk costs in the market for mobile telecommunications: the role of licence fees - Gruber, Harald (Economic & Social Studies, 2002)
An oligopoly model with endogenous sunk costs illustrates the trade off between ex ante extraction of oligopoly rents and market entry of firms in the mobile telecommunications industry. Competitive bidding for radio frequency licences provides scope for setting market structure endogenously: the higher the licence fee, the lower the number of competitive firms sustained by the market. High licence fees may be a signal for post-entry collusion.
Keywords: Mobile telecommunications; Licensing; Market structure; Oligopoly; Competition